2019
DOI: 10.31635/ccschem.019.20190001
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Structurally Defined Phosphorylated Ubiquitins Suggests Impaired Parkin Activation by Phosphorylated Ubiquitins with a Non-Phosphorylated Distal Unit

Abstract: Mutations in genes encoding PINK1 (PTEN-induced kinase 1) and Parkin (E3 ubiquitin ligase) are identified in familial Parkinson's disease. However, it remains unclear whether the phosphorylated Ub chains activate wildtype Parkin (w-Parkin) or phosphorylated Parkin (p-Parkin), with the consequent expulsion of the damaged mitochondria. To address this problem, we developed a chemical protein synthesis strategy that integrates hydrazide-based native chemical ligation, dehydroalanine conjugation, and chemoenzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

7
2

Authors

Journals

citations
Cited by 33 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…Next, we refolded the product using a standard dialysis method and collected the circular dichroism (CD) spectrum of the final product ( Extended Data Fig.1c ). The CD spectrum of the synthesized K29-linked diUb showed an ellipticity near identical to that of the ubiquitin monomer (monoUb), suggesting correct folding of the diUb 40 .…”
Section: Resultsmentioning
confidence: 85%
“…Next, we refolded the product using a standard dialysis method and collected the circular dichroism (CD) spectrum of the final product ( Extended Data Fig.1c ). The CD spectrum of the synthesized K29-linked diUb showed an ellipticity near identical to that of the ubiquitin monomer (monoUb), suggesting correct folding of the diUb 40 .…”
Section: Resultsmentioning
confidence: 85%
“…Despite these advances in recent years, some questions still need to be further answered, for example, how the remodeling activity of SMARCAD1 is activated by ubiquitinated nucleosomes or ssDNA and how SMARCAD1 removes the obstacles (such as 53BP1 and nucleosomes) through its histone dimer exchange activity. Take advantage of the recent advances in chemical protein synthesis ( McGinty et al, 2008 ; Fang et al, 2011 , 2012 ; Fierz et al, 2011 ; Siman et al, 2013 ; Li et al, 2014 , 2018 ; Morgan et al, 2016 ; Ai et al, 2019 ; Chu et al, 2019 ; Pan et al, 2019 ) and cryo-electron microscopy techniques, the biochemical and structural studies of ubiquitinated nucleosomes have recently received increasing attention ( Zhou L. et al, 2016 ; Anderson et al, 2019 ; Hsu et al, 2019 ; Jang et al, 2019 ; Park et al, 2019 ; Valencia-Sanchez et al, 2019 ; Worden and Wolberger, 2019 ; Worden et al, 2019 ; Xue et al, 2019 ; Yao et al, 2019 ; Dao et al, 2020 ). Both the in vitro reconstruction experiments and the structural analysis of the SMARCAD1-nucleosome complex may provide new insights into the remodeling mechanism of SMARCAD1.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, E2 discharge experiment showed that Ub-K6-Ub S65Pi could not transfer the Ub thioester from E2∼Ub to Parkin WT. Combination with previous works (Shiba-Fukushima et al, 2012;Koyano et al, 2014), the models of the activation of Parkin WT and phosphorylated Parkin by di-ubiquitin chains were proposed in mitophagy ( Figure 4B) (Pan et al, 2019).…”
Section: Synthesis Of Phosphorylated Di-ubiquitin and Their Applicatimentioning
confidence: 53%
“…Liu and co-workers synthesized the phosphorylated K6-linked di-ubiquitin by hydrazide-based NCL ( Figure 4A) (Pan et al, 2019). To apply this strategy, di-ubiquitin was divided into two segments, ubiquitin G76C (Ub G76C) and ubiquitin K6C (Ub K6C).…”
Section: Synthesis Of Phosphorylated Di-ubiquitin and Their Applicatimentioning
confidence: 99%